The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3390/molecules18043703
|View full text |Cite
|
Sign up to set email alerts
|

Probing Ionic Liquid Aqueous Solutions Using Temperature of Maximum Density Isotope Effects

Abstract: This work is a new development of an extensive research program that is investigating for the first time shifts in the temperature of maximum density (TMD) of aqueous solutions caused by ionic liquid solutes. In the present case we have compared the shifts caused by three ionic liquid solutes with a common cation—1-ethyl-3-methylimidazolium coupled with acetate, ethylsulfate and tetracyanoborate anions—in normal and deuterated water solutions. The observed differences are discussed in terms of the nature of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Interestingly, the TMD shifts caused by adding bulky ions to water are commensurate with those of applying positive pressure to neat water, where one finds a 2 K negative shift in the TMD per 10 MPa of applied pressure. 22 On the other hand, further studies, 23 namely in IL solutions of deuterated water, are being currently explored in order to further elucidate the relation between the strength of the hydrogen-bonded network of water and its destabilization by the different types of anion discussed in this work-more hydrophobic ([Ntf 2 ] À , [BF 4 ] À or [B(CN) 4 ] À ), more hydrophilic ([CH 3 SO 4 ] À or Cl À ), or even hydrophilic with the possibility of proton transfer ([CH 3 COO] À ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the TMD shifts caused by adding bulky ions to water are commensurate with those of applying positive pressure to neat water, where one finds a 2 K negative shift in the TMD per 10 MPa of applied pressure. 22 On the other hand, further studies, 23 namely in IL solutions of deuterated water, are being currently explored in order to further elucidate the relation between the strength of the hydrogen-bonded network of water and its destabilization by the different types of anion discussed in this work-more hydrophobic ([Ntf 2 ] À , [BF 4 ] À or [B(CN) 4 ] À ), more hydrophilic ([CH 3 SO 4 ] À or Cl À ), or even hydrophilic with the possibility of proton transfer ([CH 3 COO] À ).…”
Section: Discussionmentioning
confidence: 99%
“…Li and Kobayashi studied the ultrasound effect on aqueous 1‐butyl‐3‐methylimidazolium based ionic liquids with different anions with the help of FT‐IR spectroscopy and observed that hydrogen bonding changes on exposure of ultrasound for ionic liquids with Cl − and BF 4 − anion while there is no much effect of it on hydrogen bonding for ionic liquid with PF 6 − anion and concluded that anion plays important role for solvation when ultrasound exposed to ionic liquids. Tariq et al studied the ionic liquid – water interactions with the help of temperature of maximum density shift. They also observed that anion plays important role in hydrogen bonded network.…”
Section: Introductionmentioning
confidence: 99%
“…and having applications in medicinal chemistry, protein chemistry and furthermore have ability to dissolve biomolecules like DNA and cellulose . Many recent articles are devoted to study of hydrogen bonding between cations and anions for pure state of ionic liquids but still hydrogen bonding in the aqueous solutions of ionic liquids is limited . Li and Kobayashi studied the ultrasound effect on aqueous 1‐butyl‐3‐methylimidazolium based ionic liquids with different anions with the help of FT‐IR spectroscopy and observed that hydrogen bonding changes on exposure of ultrasound for ionic liquids with Cl − and BF 4 − anion while there is no much effect of it on hydrogen bonding for ionic liquid with PF 6 − anion and concluded that anion plays important role for solvation when ultrasound exposed to ionic liquids.…”
Section: Introductionmentioning
confidence: 99%